Purification and characterization of an agglutinin from datura innoxia with antineoplastic activity - Singh, Ruby; Nawale, Laxman; Gaikwad, Sushama M.; Suresha, C. G. (National Science Day, At CSIR-NCL, 2015)
Lectins are carbohydrate binding proteins of non-immune origin. Due to their multivalency, lectins can be easily detected using agglutination. Lectins are reported to induce cytotoxicity or inhibition of growth in various cancer cells., hence good therapeutic startegy against cancer. Factors such as specificity, stability, assay rapidity, and costs combine to make lectins attractive diagnostic reagents. Datura innoxia belongs to family of Solanaceae.All parts of the plant are hallucinogenic, hypnotic and narcotic. Application: at low dose acts as pain killer, relieves asthma and rheumatism.

Phytogenic silver, gold, and bimetallic nanoparticles as novel antitubercular agents - Singh, Richa; Nawale, Laxman; Arkile, Manisha A.; Wadhwani, Sweety; Shedbalkar, Utkarsha; Chopade, Snehal; Sarkar, Dhiman; Chopade, Balu Ananda (International Journal of Nanomedicine, 2016)
Purpose: Multi- and extensively drug-resistant tuberculosis (TB) is a global threat to human health. It requires immediate action to seek new antitubercular compounds and devise alternate strategies. Nanomaterials, in the present scenario, have opened new avenues in medicine, diagnosis, and therapeutics. In view of this, the current study aims to determine the efficacy of phytogenic metal nanoparticles to inhibit mycobacteria. Methods: Silver (AgNPs), gold (AuNPs), and gold-silver bimetallic (Au-AgNPs) nanoparticles synthesized from medicinal plants, such as Barleria prionitis, Plumbago zeylanica, and Syzygium cumini, were tested against Mycobacterium tuberculosis and M. bovis BCG. In vitro and ex vivo macrophage infection model assays were designed to determine minimum inhibitory concentration (MIC) and half maximal inhibitory concentration of nanoparticles. Microscopic analyses were carried out to demonstrate intracellular uptake of nanoparticles in macrophages. Besides this, biocompatibility, specificity, and selectivity of nanoparticles were also established with respect to human cell lines. Results: Au-AgNPs exhibited highest antitubercular activity, with MIC of <2.56 mu g/mL, followed by AgNPs. AuNPs did not show such activity at concentrations of up to 100 mu g/mL. In vitro and ex vivo macrophage infection model assays revealed the inhibition of both active and dormant stage mycobacteria on exposure to Au-AgNPs. These nanoparticles were capable of entering macrophage cells and exhibited up to 45% cytotoxicity at 30 mu g/mL (ten times MIC concentration) after 48 hours. Among these, Au-AgNPs synthesized from S. cumini were found to be more specific toward mycobacteria, with their selectivity index in the range of 94-108. Conclusion: This is the first study to report the antimycobacterial activity of AuNPs, AgNPs, and Au-AgNPs synthesized from medicinal plants. Among these, Au-AgNPs from S. cumini showed profound efficiency, specificity, and selectivity to kill mycobacteria. These should be investigated further to develop novel TB nanoantibiotics.
Keywords: Antimycobacterial agent; Cytotoxicity; drug resistance; Mycobacteria; Nanoparticles; tuberculosis